Silent life and silent language : the inner life of a mute in an institution for the deaf - Farlow, Kate M. (Gallaudet classics in deaf studies, 2018)
"Silent Life and Silent Language presents a fictionalized account of life at a Midwestern residential school for deaf students in the years following the Civil War. Based on the experiences of the author, who became deaf at the age of nine and entered a residential school when she was twelve, this historical work is remarkable and rare because it focuses on signing deaf women's lives. One of only a few accounts written by deaf women in the 19th century, Silent Life and Silent Language gives a detailed description of daily life and learning at the Indiana Asylum for the Education of the Deaf and Dumb. Kate M. Farlow wrote this book with the goal of giving hearing parents hope that their deaf children would be able to lead happy and productive lives. She sought to raise awareness of the benefits of deaf schools and was an early advocate for the use of American Sign Language and of bilingual education. The Christian influence on the school and on the author is strongly present in her writing and reflects an important component of deaf education at the time. Descriptions of specific signs, games, ASL story nights, and other aspects of the signing community during the 1870s will be of interest to modern students and researchers in linguistics, deaf education, Deaf studies, and Deaf history. Farlow's work reveals a sophisticated, early understanding of the importance of access to language, education, and community for deaf individuals"--